Feasibility and Risks of Chili Farming in Disaster-Prone Areas of Mount Merapi, Indonesia - Rahmawati, Nur; Rozaki, Zuhud; Al Riyadh, Rofiqoh Zuroida; Susanawati, Susanawati (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2023)
Mount Merapi, located in Indonesia, is an active volcano that poses a significant threat to the surrounding communities. Vegetables, including chili, are grown in the disaster-prone areas surrounding Mount Merapi, despite the risks associated with the active volcano. Based on the prevailing wind patterns in the region, the disaster-prone areas surrounding Mount Merapi have been classified into four distinct zones, namely Zones I, II, III, and IV, each characterized by distinct agroecosystems, feasibility, and risk levels. Therefore, this study aimed to describe agroecosystems, costs, income, feasibility, and risks of chili farming in in the four zones surrounding Mount Merapi. The samples of this study consist of 163 farmers from the four disaster-prone zones surrounding Mount Merapi, selected through purposive sampling. The RC ratio was employed as part of the feasibility analysis, and the production and income risks were analyzed. The results showed that chili farming in Zone IV (the area farthest from the disaster center) possessed the lowest cost, revenue, and income. On the contrary, Zone III generated the highest cost and revenue, while Zone I (the area with the highest vulnerability to disasters) had the highest income. The range of R/C values ranges from 2.40 in Zone I to 1.16 in Zone IV. Considering the results, chili farming was feasible in disaster-prone areas, where the production risk was lower than the income risk. Therefore, Zone I, the area with extremely high disaster risk, had the lowest production and income risk. This study highlighted that chili farming provides benefits to the vulnerable farmers and new perspective for agricultural sustainability in the area of Mount Merapi.